PEMBERDAYAAN PESERTA DIDIK PAKET C MELALUI PELATIHAN PEMBUATAN BRIKET DARI LIMBAH PABRIK KAYU DI PKBM MANHAJUL HUSNA, KELURAHAN ALALAK, KECAMATAN BANJARMASIN UTARA - Mahmuda Mahmuda (Al-Manba, 2025)
This study aims to describe the process and impact of briquette-making training using wood factory waste as a form of empowerment for Paket C learners at PKBM Manhajul Husna, Alalak Sub-district, North Banjarmasin District. The training program was designed to enhance vocational skills and environmental awareness by utilizing industrial waste into an alternative energy source. This research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the training successfully improved the learners’ knowledge and skills in processing wood waste into briquettes and fostered entrepreneurial spirit among them. Moreover, the program strengthened the role of non-formal education in addressing local environmental and economic issues. This training is considered effective as an empowerment strategy and is recommended to be replicated in other community learning centers (PKBM).